Social Vision: Applying a Social-Functional Approach to Face and Expression Perception. (June 2017) - Adams, Reginald B.; Albohn, Daniel N.; Kveraga, Kestutis
A social-functional approach to face processing comes with a number of assumptions. First, given that humans possess limited cognitive resources, it assumes that we naturally allocate attention to processing and integrating the most adaptively relevant social cues. Second, from these cues, we make behavioral forecasts about others in order to respond in an efficient and adaptive manner. This assumption aligns with broader ecological accounts of vision that highlight a direct action-perception link, even for nonsocial vision. Third, humans are naturally predisposed to process faces in this functionally adaptive manner. This latter contention is implied by our attraction to dynamic aspects of the face, including looking behavior and facial expressions, from which we tend to overgeneralize inferences, even when forming impressions of stable traits. The functional approach helps to address how and why observers are able to integrate functionally related compound social cues in a manner that is ecologically relevant and thus adaptive.